2017
DOI: 10.1111/acel.12680
|View full text |Cite
|
Sign up to set email alerts
|

miR‐155 induces ROS generation through downregulation of antioxidation‐related genes in mesenchymal stem cells

Abstract: SummaryInflammation‐induced reactive oxygen species (ROS) are implicated in cellular dysfunction and an important trigger for aging‐ or disease‐related tissue degeneration. Inflammation‐induced ROS in stem cells lead to deterioration of their properties, altering tissue renewal or regeneration. Pathological ROS generation can be induced by multiple steps, and dysfunction of antioxidant systems is a major cause. The identification of the central molecule mediating the above‐mentioned processes would pave the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 45 publications
(51 reference statements)
1
48
0
Order By: Relevance
“…In addition to the above‐mentioned analyses, ChIP‐Atlas Enrichment Analysis (formerly designated “ in silico ChIP”) has been used for various other purposes. For example, this tool has been applied to analyze TR enrichment at genomic ROIs such as expression quantitative trait loci (eQTLs), a user's own ChIP‐seq peak‐call data, and evolutionarily accelerated regions as well as genes whose expression levels are changed by drug exposure, aging, or cancer development (see http://chip-atlas.org/publications for the full list of publications citing ChIP‐Atlas). The results generated by ChIP‐Atlas are all assigned unique URLs (see ChIP‐Atlas document in https://github.com/inutano/chip-atlas/wiki for details) and are publicly available, and they are thus ready for sharing seamlessly among researchers for subsequent analysis in command lines and for interconnecting with other biodatabases such as the DeepBlue Epigenomic Data Server and RegulatorTrail , where ChIP‐Atlas data have been imported and subjected to analyses.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the above‐mentioned analyses, ChIP‐Atlas Enrichment Analysis (formerly designated “ in silico ChIP”) has been used for various other purposes. For example, this tool has been applied to analyze TR enrichment at genomic ROIs such as expression quantitative trait loci (eQTLs), a user's own ChIP‐seq peak‐call data, and evolutionarily accelerated regions as well as genes whose expression levels are changed by drug exposure, aging, or cancer development (see http://chip-atlas.org/publications for the full list of publications citing ChIP‐Atlas). The results generated by ChIP‐Atlas are all assigned unique URLs (see ChIP‐Atlas document in https://github.com/inutano/chip-atlas/wiki for details) and are publicly available, and they are thus ready for sharing seamlessly among researchers for subsequent analysis in command lines and for interconnecting with other biodatabases such as the DeepBlue Epigenomic Data Server and RegulatorTrail , where ChIP‐Atlas data have been imported and subjected to analyses.…”
Section: Resultsmentioning
confidence: 99%
“…This tool is also able to accept a batch of gene symbols and can therefore discover TFs that collectively regulate the gene set of interest (e.g. Chatterjee et al 2018;Onodera et al 2017;Chen et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR‐335 leads to cellular senescence of MSCs as evidenced by increased SA‐β‐gal activity and p16 protein level and decreased cell proliferation, impairing the immunomodulatory capacity, and differentiation capacity (Tome et al, 2014). Importantly, Onodera et al (2017) reported that the expression level of miR‐155‐5p is significantly enhanced in MSCs isolated from aged mice compared with MSCs collected from young mice. Consistent with these findings, we observed that miR‐155‐5p was significantly increased in human AMSCs and serum from aging donors in the current study, suggesting that miR‐155‐5p may be a potential factor in regulating MSC senescence.…”
Section: Discussionmentioning
confidence: 99%